Medullary Thyroid Cancer: Is the Adequacy of Pre-Operative Evaluation Influenced by Training Background? - Amal Alhefdhi; Sarah C. Oltmann; Herbert Chen; Rebecca S. Sippel (Journal of Thyroid Cancer, 2015)
Background: Medullary Thyroid Cancer (MTC) is a rare malignancy, accounting for less than 3% of all thyroid cancers and causes significant morbidity and mortality. MTC is often due to an underlying mutation of the RET proto-oncogene, which can result in additional endocrinopathies that must be screened for pre-operatively. The project aim was to determine if surgical training background influenced patient pre-operative evaluation for MTC. Methods: A retrospective review was performed of patients undergoing thyroidectomy for MTC at a single academic institution. Patients were analyzed based on who performed the initial operative procedure, a surgeon with specific endocrine surgery training or a surgeon without. Results: From 1994 to 2011, 37 patients with MTC were identified. Thirty percent were managed by an endocrine surgeon and 70% by a non-endocrine surgeon. A complete thyroid work-up was done for all the patients managed by an endocrine surgeon vs. 38.5% of the non-endocrine surgeon patients (p<0.01). Appropriate preoperative endocrine screening was performed in 91% of the endocrine surgeon patients vs. 50% of the non-endocrine surgeon patients (p= 0.03). RET mutation genetic testing was done for all endocrine surgeon patients vs. 85% of non-endocrine surgeon patients (p= 0.30). Conclusion: Endocrine trained surgeons recognize and appropriately manage the complexity of MTC and associated endocrinopathies, more often than surgeons without an endocrine surgery background. This may result in optimized management of these patients.
Keywords: Medullary Thyroid Cancer